Real-time IncuCyte® Assay for the Dynamic Assessment of Live and Dead Cells in 2D Cultures - Arlene Gidda; Suganthi Chittaranjan; Sharon Gorski (Bio-Protocol)
Cell viability and cytotoxicity assays are commonly used to investigate protein function and to evaluate drug efficacy in cancer and other disease models. Cytotoxicity is the measure of dead or damaged cells and is often quantified using assays based on cellular characteristics such as membrane integrity or mitochondrial metabolism. However, these assays are typically limited to endpoint analysis and lack emulation of physiological conditions. The IncuCyte Live and Dead Cell assay described here leverages common cell permeability methodologies but uses fluorescence microscopy channels to image both live and dead cells over time and phase microscopy channels to measure confluency. Cytotox green reagent is a cell membrane–impermeable dye that can only be taken up by cells with poor cell membrane integrity. NucLight rapid red dye is a cell membrane–permeable nuclear dye that can be taken up by all cells. Based on dye uptake and fluorescence intensity, the IncuCyte software can be used to analyze images for live and dead cell detection and quantification. Phase microscopy is used to determine confluency and can be further quantified using the IncuCyte software. We provide an application of this assay, using it to calculate IC50 and EC50 values for the assessment of drug efficacy.